Two Voices in the Same Habitat: Habima as Seen through the Works of Baruch Tchemerinsky and Zvi Friedland - Yeroushalmi, Dorit (MiKAN, 2006)
The early research on Habima gave pride of place to local plays andflag performances, while the issue of directors and direction waspushed aside. However, during the period of the British Mandateonly a few local plays found their way to Habima's stage; and it wasnot these works that established the image of what was "theatre",but rather the work and directorial approaches of the directors. Thisarticle deconstructs the "old-fashioned" image that has long adheredto Habima's narrative. In terms of the works of Baruch Tchemerinskyand Zvi Friedland, it was not "old-fashioned", but, rather, a theatrethat spoke in different voices - voices that constituted part of theongoing cultural engineering processes.